Immuno-Spin Trapping-Based Detection of Oxidative Modifications in Cardiomyocytes and Coronary Endothelium in the Progression of Heart Failure in Tgαq*44 Mice - Proniewski, Bartosz; Czarny, Joanna; Khomich, Tamara I.; Kus, Kamil; Zakrzewska, Agnieszka; Chlopicki, Stefan (Frontiers in Immunology, 2018)
Recent studies suggest both beneficial and detrimental role of increased reactive oxygen species and oxidative stress in heart failure. However, it is not clear at which stage oxidative stress and oxidative modifications occur in the endothelium in relation to cardiomyocytes in non-ischemic heart failure. Furthermore, most methods used to date to study oxidative stress are either nonspecific or require tissue homogenization. In the present study, we used immuno-spin trapping technique with fluorescent microscopy‑based detection of DMPO nitrone adducts to localize and quantify oxidative modifications of the hearts from Tgαq*44 mice, a murine model of heart failure driven by cardiomyocyte-specific overexpression of Gαq* protein. Tgαq*44 mice and age‑matched FVB controls at early, transition and late stages of heart failure progression were injected with DMPO in vivo and analysed ex vivo for DMPO nitrone adducts signals. Progressive oxidative modifications in cardiomyocytes, as evidenced by the elevation of DMPO nitrone adducts, was detected in hearts from 10-16-month-old, but not in 8-month-old Tgαq*44 mice, as compared with age-matched FVB mice. The DMPO nitrone adducts were detected in left and right ventricle, septum and papillary muscle. Surprisingly, significant elevation of DMPO nitrone adducts were also present in the coronary endothelium both in large arteries and in microcirculation simultaneously as in cardiomyocytes starting from 10-month-old Tgαq*44 mice. On the other hand, superoxide production in heart homogenates was elevated already in 6‑month-old Tgαq*44 mice and progressively increased to high levels in 14‑month‑old Tgαq*44 mice, while the enzymatic activity of catalase, glutathione reductase and glutathione peroxidase were all elevated as early as in 4-month-old Tgαq*44 mice and stayed at a similar level in 14‑month‑old Tgαq*44. In summary, the present study demonstrates that immuno-spin trapping represents a unique method that allows to quantify oxidative modifications in cardiomyocytes and coronary endothelium in the heart. In Tgαq*44 mice with slowly developing heart failure, driven by cardiomyocyte-specific overexpression of Gαq* protein, an increase in superoxide production, despite compensatory activation of antioxidative mechanisms, results in the development of oxidative modifications not only in cardiomyocytes, but also in coronary endothelium, at the transition phase of heart failure prior to the end-stage disease.